2007
DOI: 10.1074/jbc.m703748200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Structural and Functional Roles of Conserved Residues in the First Extracellular Domain of Receptors for Corticotropin-releasing Factor and Related G-protein-coupled Receptors

Abstract: The G-protein-coupled receptor B1 family includes corticotropin-releasing factor (CRF), growth hormone-releasing hormone, incretin, and pituitary adenylate cyclase-activating polypeptide receptors. The three-dimensional NMR structure of the first extracellular domain (ECD1) of CRF receptor 2␤ (CRF-R2␤), free and complexed with astressin, comprises a Sushi domain. This domain is stabilized in part by a salt bridge between Asp 65 and Arg 101 . Analogous residues are conserved in other members of the B1 family. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…6). This model is consistent with the NMR structure of the CRFR2 N-terminal extracellular domain (28), with the functional data showing full binding capacity of the N-terminal extracellular domain (15,28,30,31,40,41,45,48,50), and with the cross-linking data of Bpa-substituted UCN1 at positions 17 and 22, which showed crosslinking to the first extracellular loop (26). However, the model does not fit the cross-linking data of Bpa-substituted at position 0 and 12, which showed cross-linking to the second extracellular loop (26).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…6). This model is consistent with the NMR structure of the CRFR2 N-terminal extracellular domain (28), with the functional data showing full binding capacity of the N-terminal extracellular domain (15,28,30,31,40,41,45,48,50), and with the cross-linking data of Bpa-substituted UCN1 at positions 17 and 22, which showed crosslinking to the first extracellular loop (26). However, the model does not fit the cross-linking data of Bpa-substituted at position 0 and 12, which showed cross-linking to the second extracellular loop (26).…”
Section: Discussionsupporting
confidence: 72%
“…Cross-linking with Bpa-substituted UCN1 analogs showed that a Bpa group located at positions 0 or 12 cross-links to the second extracellular receptor loop, whereas Bpa at positions 17 or 22 cross-links to the first extracellular receptor loop (26); these data suggest that the N terminus of UCN1 binds closer to the CRFR1 extracellular surface. It is also possible that UCN1 binding to CRFR1 expressed in mammalian cells as shown by UCN1 cross-linking (26) is different from the binding of the free N-terminal extracellular domain of CRFR1, which is shown to be both necessary and sufficient for binding N-terminally truncated CRF, sauvagine, and UCN1 based analogs (15,28,30,31,40,41,45,48,50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same packing interactions of these conserved residues are observed in all crystal structures of class B GPCR ECDs solved to date (30 -32). We see no evidence for a salt bridge between Arg 85 and Asp 49 as proposed for the equivalent residues in the mCRFR2␤ ECD (29,47).…”
Section: Expression and Purification Of The Crfr1 Ecd As An Mbp Fusiomentioning
confidence: 80%